2012
DOI: 10.1017/s0033291712000220
|View full text |Cite
|
Sign up to set email alerts
|

Do all schizophrenia patients need antipsychotic treatment continuously throughout their lifetime? A 20-year longitudinal study

Abstract: BackgroundThe prevailing standard of care in the field involves background assumptions about the importance of prolonged use of antipsychotic medications for all schizophrenia (SZ) patients. However, do all SZ patients need antipsychotics indefinitely? Are there factors that help to identify which SZ patients can enter into prolonged periods of recovery without antipsychotics? This 20-year longitudinal research studied these issues. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
121
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 56 publications
12
121
0
3
Order By: Relevance
“…These authors published several papers [45,46,48,49] that examined patients with schizophrenia who were either on or off antipsychotic medications over a 15-to 20-year study period, and found that those who got off antipsychotics, as a group, had much better outcomes. More specifically, over the long term, patients with schizophrenia not prescribed antipsychotics had statistically significantly less psychotic symptoms (p \ 0.05) [45,46], more periods of remission [47] or recovery (p \ 0.05) [45,48,49], and a better global functioning (p \ 0.001) [46] than those prescribed antipsychotics. This surprising finding led these authors to suggest a 'recovery paradox' in which antipsychotics help in the short term, but may lose efficacy in the long term.…”
Section: Results Of Descriptivementioning
confidence: 99%
See 1 more Smart Citation
“…These authors published several papers [45,46,48,49] that examined patients with schizophrenia who were either on or off antipsychotic medications over a 15-to 20-year study period, and found that those who got off antipsychotics, as a group, had much better outcomes. More specifically, over the long term, patients with schizophrenia not prescribed antipsychotics had statistically significantly less psychotic symptoms (p \ 0.05) [45,46], more periods of remission [47] or recovery (p \ 0.05) [45,48,49], and a better global functioning (p \ 0.001) [46] than those prescribed antipsychotics. This surprising finding led these authors to suggest a 'recovery paradox' in which antipsychotics help in the short term, but may lose efficacy in the long term.…”
Section: Results Of Descriptivementioning
confidence: 99%
“…One author [33] even states that an estimated 25-40 % of acute psychoses remit without antipsychotic treatment, referring to recovery rates reported by several long-term follow-up studies [19,[41][42][43][44], in most cases conducted prior to the widespread use of antipsychotic drugs. Several more recent long-term (C10 years) naturalistic or observational follow-up studies [45][46][47][48][49] suggest that, longitudinally, patients with schizophrenia not prescribed antipsychotics experience more periods of remission or recovery and better global functioning than those prescribed continuous antipsychotic treatment. The buildup of dopamine supersensitivity and tolerance to antipsychotics [50][51][52][53] would lead to treatment failure over time [54].…”
Section: Introductionmentioning
confidence: 99%
“…Harrow et al [8] examined this assumed paradigm in a 20-year longitudinal study of 70 patients with schizophrenia and 69 patients with mood disorders. These patients were prospectively assessed at baseline and then 6 times over the next 20 years for major symptoms, psychosocial functioning, personality, attitudinal variables, neurocognition and treatment.…”
Section: Treatment Of Schizophreniamentioning
confidence: 99%
“…There also seem to be major contradictions between the principles of CCGS and those of NAA, which was the focus of this research. In the paragraphs below I shall present a critical evaluation of CCGS.Scientific discussion has indicated a need to reconsider the role of antipsychotic medication -and indeed the entire biogenetic paradigm of psychiatry (Bracken et al, 2012;Harrow, Jobe, & Faull, 2012;Lepping et al, 2011;Morrison et al, 2012;Priebe, Burns, & Craig, 2013). This is not reflected in CCGS, with the updates moving rather in the opposite direction.…”
mentioning
confidence: 99%